2008
DOI: 10.1029/2008gl034365
|View full text |Cite
|
Sign up to set email alerts
|

Joint modeling of lithosphere and mantle dynamics elucidating lithosphere‐mantle coupling

Abstract: We provide new insights into the lithosphere‐mantle coupling problem through a joint modeling of lithosphere dynamics and mantle convection and through comparison of model results with the high resolution velocity gradient tensor model along the Earth's plate boundary zones. Using a laterally variable effective viscosity lithosphere model, we compute depth integrated deviatoric stresses associated with both gravitational potential energy (GPE) differences and deeper mantle density buoyancy‐driven convection. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
119
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(125 citation statements)
references
References 16 publications
5
119
1
Order By: Relevance
“…Deriving all force contributions from a single calculation resolves any inconsistency that might arise from treating individual force contributions to the stress field separately, as has been done in earlier studies (Bird et al, 2008;Steinberger et al, 2001;Lithgow-Bertelloni and Guynn, 2004;Ghosh et al, 2008;Naliboff et al, 2012;Ghosh et al, 2013;Wang et al, 2015).…”
Section: Introductionmentioning
confidence: 92%
“…Deriving all force contributions from a single calculation resolves any inconsistency that might arise from treating individual force contributions to the stress field separately, as has been done in earlier studies (Bird et al, 2008;Steinberger et al, 2001;Lithgow-Bertelloni and Guynn, 2004;Ghosh et al, 2008;Naliboff et al, 2012;Ghosh et al, 2013;Wang et al, 2015).…”
Section: Introductionmentioning
confidence: 92%
“…An alternative method documented in the literature is to compare the strain rate estimated from the modeled deviatoric stresses (Ghosh et al, 2008) with the Global Strain Rate Map (Kreemer et al, 2003). However, the lithospheric stress in plate interiors (i.e., far from the plate boundaries) is not well constrained with the Global Strain Rate Map.…”
mentioning
confidence: 99%
“…On the one hand, Bird et al (2008) have estimated the lithospheric stress from a model that disregards the mantle flow contribution and used the fit between modeled and observed plate velocities as a sole criterion. On the other hand, Ghosh et al (2013), Ghosh and Holt (2012), Lithgow-Bertelloni and Guynn (2004), Steinberger et al (2001) and Wang et al (2015) have aimed at assessing the influence of mantle flow on the lithospheric stress field and have shown that the bulk mantle flow explains a large part (about 80-90 %) of the stress field accumulated in the lithosphere (Steinberger et al, 2001), in both magnitude and the most compressive horizontal direction. The aim of the present study is to evaluate the contribution of the upper mantle density and viscosity heterogeneities above the transition zone to the observed spatial stress regimes of the lithosphere (Heidbach et al, 2016), while testing different approaches and data sets used to describe the thermal and rheological structure of the upper mantle and the crust.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Few studies have tried to address this question by modelling both sources [69][70][71][72][73][74] . These studies showed that coupling depends on the viscosity variations.…”
Section: Forces Driving Plate Tectonicsmentioning
confidence: 99%